Conjunctival Extranodal Natural Killer/T-Cell Lymphoma, Nasal Type. Issue 6 (June 2015) - Kiratli, Hayyam; Uzun, Salih; Yeşilirmak, Aysun; Ayhan, Arzu Sağlam; Soylemezoğlu, Figen
Abstract : Purpose: To report a rare case of a patient with isolated primary conjunctival extranodal natural killer/T-cell lymphoma, nasal type (ENKTCL) without nasal involvement. Methods: The clinical course, magnetic resonance imaging, positron emission tomographic and immunohistopathological features of the patient were evaluated. Results: A 57-year-old man presented with rapidly progressing swelling and redness in his right eye for 2 months. A salmon-colored mass was present under all parts of the bulbar conjunctiva. Magnetic resonance imaging demonstrated a mass anterior to the globe without any sinus involvement. Positron emission tomographic study did not show other disease sites. Immunohistopathological studies on incisional biopsy specimen demonstrated ENKTCL with positive CD2, CD7, CD56, bcl-2, and T cell–restricted intracellular antigen, and negative CD20, CD8, CD123, and terminal deoxynucleotidyl transferase staining. Epstein–Barr virus (EBV)–encoded mRNA was also diffusely positive. Ki-67 index was more than 90%. The patient received cyclophosphamide, vincristine, hydroxydaunorubicin, cisplatin, and prednisone chemotherapy with 4500 cGY radiotherapy in 25 fractions to the right orbit, resulting in total resolution of the conjunctival tumor. He developed intracranial and gastrointestinal tumors and died of cardiopulmonary failure 11 months later. Conclusions: Extranodal natural killer/T-cell lymphoma, nasal type may primarily arise in the conjunctiva without nasal or paranasal sinus involvement. Despite initial successful local tumor control by systemic chemotherapy and local irradiation, the overall prognosis is poor due to systemic dissemination.